ASSESSMENT OF EFFECTIVE UPTAKE OF TeleMANAS SERVICE IN INDIA - Singh.A; Chopra.M; Singh.R.S (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
To provide universal access to equitable, accessible, affordable and quality mental health care through 24X7 and extending the mental health services to vulnerable groups of the population and difficult to reach populations. Government of India (GoI) in its Union Budget 2022, announced the National Tele Mental Health Programme of India, Tele Mental Health Assistance and Networking Across States (Tele MANAS) and entrusted the Ministry of Health and Family Welfare (MoHFW) to guide its overall implementation. Consequently, the MoHFW formed a National Technical Advisory Group (NTAG) and three technical advisory sub-committees (Mental Health Service Delivery, Information Technology Architecture and Health Systems) to achieve specific goals and objectives of Tele MANAS. This study aims at assessing awareness and determining the effective uptake of the service among the community. It was a cross-sectional study conducted among individuals aged 18 and above in Chandigarh, India with the sample size of 332 participants, and data was collected using a structured questionnaire. The results show the urgency of mental health care. Also, showed a drastic change in the perception and knowledge of individuals regarding the TeleMANAS service. The ethical clearance was taken from the competent authority for the conduct of the research along with individual participation consent.